Камень, глина и фантазия: книга для учащихся / Л. И. Данилова - Данилова Людмила Ивановна (Просвещение, 1991)
Экземпляры: аб. ДБ (1991) / Инвентарный номер: 33629 / Цена: / Сис.шифр: 85.11 / Авт.знак: Д 18 / ББК: 85.11